Educating Together, Improving Together: Harmonizing Interprofessional Approaches to Address the Opioid Epidemic - National Academy of Medicine (The National Academies Press, 2021)
The United States is in the midst of an urgent and complex opioid crisis. To address how education and training can more effectively respond to this crisis, we must have a better understanding of problems in practice2014or professional practice gaps2014for health professionals and teams in practice. A coordinated response requires identifying and addressing professional practice gaps (PPGs) related to pain management, opioid use disorder, and other substance use disorder (SUD) care, as well as integrating evidence-based best practices into health professional education and training curricula across the continuum from undergraduate training into post-graduate continuing education This Special Publication presents two information-gathering efforts to assess persisting PPGs pertaining to pain management and SUD care and to better understand the current health professional education environment: the first is a comprehensive literature review, and the second is a survey of the regulatory landscape.The results underscore the need to collaboratively develop a harmonized interprofessional, person- and family-centered approach for the continuum of health professions education to more effectively address the opioid crisis.In this Special Publication, the Health Professional Education and Training Workgroup of the National Academy of Medicine2019s Action Collaborative on Countering the U.S. Opioid Epidemic identified five action-oriented priorities to support this goal:Establish minimum core competencies in pain management and substance use disorders for all health care professionals, and support tracking of health care professionals2019 competenceAlign accreditors' expectations for interprofessional collaboration in education for pain management and substance use disordersFoster interprofessional collaboration among licensing and certifying bodies to optimize regulatory approaches and outcomesUnleash the capacity for continuing education to meet health professions learners where they are through investment and leadership, andCollaborate to harmonize practice improvement initiativesWith due effort and support, these approaches will amplify effective practices while harmonizing and improving the environment for health care professionals to best serve the needs of their patients and communities.

Pain Management and the Opioid Epidemic: Balancing Societal and Individual Benefits and Risks of Prescription Opioid Use - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2017)
Drug overdose, driven largely by overdose related to the use of opioids, is now the leading cause of unintentional injury death in the United States. The ongoing opioid crisis lies at the intersection of two public health challenges: reducing the burden of suffering from pain and containing the rising toll of the harms that can arise from the use of opioid medications. Chronic pain and opioid use disorder both represent complex human conditions affecting millions of Americans and causing untold disability and loss of function. In the context of the growing opioid problem, the U.S. Food and Drug Administration (FDA) launched an Opioids Action Plan in early 2016. As part of this plan, the FDA asked the National Academies of Sciences, Engineering, and Medicine to convene a committee to update the state of the science on pain research, care, and education and to identify actions the FDA and others can take to respond to the opioid epidemic, with a particular focus on informing FDA's development of a formal method for incorporating individual and societal considerations into its risk-benefit framework for opioid approval and monitoring.

Relieving Pain in America: A Blueprint for Transforming Prevention, Care, Education, and Research - Institute of Medicine (The National Academies Press, 2011)
Chronic pain costs the nation up to 635 billion each year in medical treatment and lost productivity. The 2010 Patient Protection and Affordable Care Act required the Department of Health and Human Services (HHS) to enlist the Institute of Medicine (IOM) in examining pain as a public health problem. In this report, the IOM offers a blueprint for action in transforming prevention, care, education, and research, with the goal of providing relief for people with pain in America. To reach the vast multitude of people with various types of pain, the nation must adopt a population-level prevention and management strategy. The IOM recommends that HHS develop a comprehensive plan with specific goals, actions, and timeframes. Better data are needed to help shape efforts, especially on the groups of people currently underdiagnosed and undertreated, and the IOM encourages federal and state agencies and private organizations to accelerate the collection of data on pain incidence, prevalence, and treatments. Because pain varies from patient to patient, healthcare providers should increasingly aim at tailoring pain care to each person's experience, and self-management of pain should be promoted. In addition, because there are major gaps in knowledge about pain across health care and society alike, the IOM recommends that federal agencies and other stakeholders redesign education programs to bridge these gaps. Pain is a major driver for visits to physicians, a major reason for taking medications, a major cause of disability, and a key factor in quality of life and productivity. Given the burden of pain in human lives, dollars, and social consequences, relieving pain should be a national priority.

The Health Effects of Cannabis and Cannabinoids: The Current State of Evidence and Recommendations for Research - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2017)
Significant changes have taken place in the policy landscape surrounding cannabis legalization, production, and use. During the past 20 years, 25 states and the District of Columbia have legalized cannabis and\/or cannabidiol (a component of cannabis) for medical conditions or retail sales at the state level and 4 states have legalized both the medical and recreational use of cannabis. These landmark changes in policy have impacted cannabis use patterns and perceived levels of risk. However, despite this changing landscape, evidence regarding the short- and long-term health effects of cannabis use remains elusive. While a myriad of studies have examined cannabis use in all its various forms, often these research conclusions are not appropriately synthesized, translated for, or communicated to policy makers, health care providers, state health officials, or other stakeholders who have been charged with influencing and enacting policies, procedures, and laws related to cannabis use. Unlike other controlled substances such as alcohol or tobacco, no accepted standards for safe use or appropriate dose are available to help guide individuals as they make choices regarding the issues of if, when, where, and how to use cannabis safely and, in regard to therapeutic uses, effectively. Shifting public sentiment, conflicting and impeded scientific research, and legislative battles have fueled the debate about what, if any, harms or benefits can be attributed to the use of cannabis or its derivatives, and this lack of aggregated knowledge has broad public health implications. The Health Effects of Cannabis and Cannabinoids provides a comprehensive review of scientific evidence related to the health effects and potential therapeutic benefits of cannabis. This report provides a research agenda2014outlining gaps in current knowledge and opportunities for providing additional insight into these issues2014that summarizes and prioritizes pressing research needs.

Ending Discrimination Against People with Mental and Substance Use Disorders: The Evidence for Stigma Change - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
Estimates indicate that as many as 1 in 4 Americans will experience a mental health problem or will misuse alcohol or drugs in their lifetimes. These disorders are among the most highly stigmatized health conditions in the United States, and they remain barriers to full participation in society in areas as basic as education, housing, and employment. Improving the lives of people with mental health and substance abuse disorders has been a priority in the United States for more than 50 years. The Community Mental Health Act of 1963 is considered a major turning point in America's efforts to improve behavioral healthcare. It ushered in an era of optimism and hope and laid the groundwork for the consumer movement and new models of recovery. The consumer movement gave voice to people with mental and substance use disorders and brought their perspectives and experience into national discussions about mental health. However over the same 50-year period, positive change in American public attitudes and beliefs about mental and substance use disorders has lagged behind these advances. Stigma is a complex social phenomenon based on a relationship between an attribute and a stereotype that assigns undesirable labels, qualities, and behaviors to a person with that attribute. Labeled individuals are then socially devalued, which leads to inequality and discrimination. This report contributes to national efforts to understand and change attitudes, beliefs and behaviors that can lead to stigma and discrimination. Changing stigma in a lasting way will require coordinated efforts, which are based on the best possible evidence, supported at the national level with multiyear funding, and planned and implemented by an effective coalition of representative stakeholders. Ending Discrimination Against People with Mental and Substance Use Disorders: The Evidence for Stigma Change explores stigma and discrimination faced by individuals with mental or substance use disorders and recommends effective strategies for reducing stigma and encouraging people to seek treatment and other supportive services. It offers a set of conclusions and recommendations about successful stigma change strategies and the research needed to inform and evaluate these efforts in the United States.

Medication-Assisted Treatment for Opioid Use Disorder: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
On October 30 and 31, 2018, the National Academies of Sciences, Engineering, and Medicine held a 1.5-day workshop on Medication-Assisted Treatment (MAT) for Opioid Use Disorder (OUD). The workshop participants reviewed the current knowledge and gaps in understanding regarding the effectiveness of MAT for treating OUD, examined the available evidence on the range of parameters and circumstances in which MAT can be effectively delivered (e.g., duration of treatment, populations, settings, and interventions to address social determinants of health as a component of MAT), identified challenges in implementation and additional research needed. This publication summarizes the presentations and discussions from the workshop.

Substance Use Disorders in the U.S. Armed Forces - Institute of Medicine (The National Academies Press, 2013)
Problems stemming from the misuse and abuse of alcohol and other drugs are by no means a new phenomenon, although the face of the issues has changed in recent years. National trends indicate substantial increases in the abuse of prescription medications. These increases are particularly prominent within the military, a population that also continues to experience long-standing issues with alcohol abuse. The problem of substance abuse within the military has come under new scrutiny in the context of the two concurrent wars in which the United States has been engaged during the past decade2014in Afghanistan (Operation Enduring Freedom) and Iraq (Operation Iraqi Freedom and Operation New Dawn). Increasing rates of alcohol and other drug misuse adversely affect military readiness, family readiness, and safety, thereby posing a significant public health problem for the Department of Defense (DoD). To better understand this problem, DoD requested that the Institute of Medicine (IOM) assess the adequacy of current protocols in place across DoD and the different branches of the military pertaining to the prevention, screening, diagnosis, and treatment of substance use disorders (SUDs). Substance Use Disorders in the U.S. Armed Forces reviews the IOM's task of assessing access to SUD care for service members, members of the National Guard and Reserves, and military dependents, as well as the education and credentialing of SUD care providers, and offers specific recommendations to DoD on where and how improvements in these areas could be made.

Pain Management for People with Serious Illness in the Context of the Opioid Use Disorder Epidemic: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
The United States is facing an opioid use disorder epidemic with opioid overdoses killing 47,000 people in the U.S. in 2017. The past three decades have witnessed a significant increase in the prescribing of opioids for pain, based on the belief that patients were being undertreated for their pain, coupled with a widespread misunderstanding of the addictive properties of opioids. This increase in prescribing of opioids also saw a parallel increase in addiction and overdose. In an effort to address this ongoing epidemic of opioid misuse, policy and regulatory changes have been enacted that have served to limit the availability of prescription opioids for pain management. Overlooked amid the intense focus on efforts to end the opioid use disorder epidemic is the perspective of clinicians who are experiencing a significant amount of daily tension as opioid regulations and restrictions have limited their ability to treat the pain of their patients facing serious illness. Increased public and clinician scrutiny of opioid use has resulted in patients with serious illness facing stigma and other challenges when filling prescriptions for their pain medications or obtaining the prescription in the first place. Thus clinicians, patients, and their families are caught between the responses to the opioid use disorder epidemic and the need to manage pain related to serious illness. The National Academies of Sciences, Engineering, and Medicine sponsored a workshop on November 29, 2018, to examine these unintended consequences of the responses to the opioid use disorder epidemic for patients, families, communities, and clinicians, and to consider potential policy opportunities to address them. This publication summarizes the presentations and discussions from the workshop.

Medications for Opioid Use Disorder Save Lives - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
The opioid crisis in the United States has come about because of excessive use of these drugs for both legal and illicit purposes and unprecedented levels of consequent opioid use disorder (OUD). More than 2 million people in the United States are estimated to have OUD, which is caused by prolonged use of prescription opioids, heroin, or other illicit opioids. OUD is a life-threatening condition associated with a 20-fold greater risk of early death due to overdose, infectious diseases, trauma, and suicide. Mortality related to OUD continues to escalate as this public health crisis gathers momentum across the country, with opioid overdoses killing more than 47,000 people in 2017 in the United States. Efforts to date have made no real headway in stemming this crisis, in large part because tools that already exist2014like evidence-based medications2014are not being deployed to maximum impact. To support the dissemination of accurate patient-focused information about treatments for addiction, and to help provide scientific solutions to the current opioid crisis, this report studies the evidence base on medication assisted treatment (MAT) for OUD. It examines available evidence on the range of parameters and circumstances in which MAT can be effectively delivered and identifies additional research needed.

Living Well with Chronic Illness: A Call for Public Health Action - Institute of Medicine (The National Academies Press, 2012)
In the United States, chronic diseases currently account for 70 percent of all deaths, and close to 48 million Americans report a disability related to a chronic condition. Today, about one in four Americans have multiple diseases and the prevalence and burden of chronic disease in the elderly and racial\/ethnic minorities are notably disproportionate. Chronic disease has now emerged as a major public health problem and it threatens not only population health, but our social and economic welfare. Living Well with Chronic Disease identifies the population-based public health actions that can help reduce disability and improve functioning and quality of life among individuals who are at risk of developing a chronic disease and those with one or more diseases. The book recommends that all major federally funded programmatic and research initiatives in health include an evaluation on health-related quality of life and functional status. Also, the book recommends increasing support for implementation research on how to disseminate effective longterm lifestyle interventions in community-based settings that improve living well with chronic disease. Living Well with Chronic Disease uses three frameworks and considers diseases such as heart disease and stroke, diabetes, depression, and respiratory problems. The book's recommendations will inform policy makers concerned with health reform in public- and private-sectors and also managers of communitybased and public-health intervention programs, private and public research funders, and patients living with one or more chronic conditions.

Integrating Responses at the Intersection of Opioid Use Disorder and Infectious Disease Epidemics: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
According to the Centers for Disease Control and Prevention (CDC), 115 Americans die each day from an opioid overdose, which averages one death every 12.5 minutes. Between 1999 and 2016, the number of drug overdoses catapulted by 300 percent, with injection drug use increasing by 93 percent between 2004 and 2014 and opioid-related hospital admissions increasing by 58 percent over the past decade. And an inexorable sequela of the opioid epidemic is the spread of infectious diseases. To address these infectious disease consequences of the opioid crisis, a public workshop titled Integrating Infectious Disease Considerations with Response to the Opioid Epidemic was convened on March 12 and 13, 2018, by the National Academies of Sciences, Engineering, and Medicine. Participants discussed strategies to prevent and treat infections in people who inject drugs, especially ways to work efficiently though the existing public health and medical systems. This publication summarizes the presentations and discussions from the workshop.

Measuring Recovery from Substance Use or Mental Disorders: Workshop Summary - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
In February 2016, the National Academies of Sciences, Engineering, and Medicine held a workshop to explore options for expanding the Substance Abuse and Mental Health Services Administration2019s (SAMHSA) behavioral health data collections to include measures of recovery from substance use and mental disorder. Participants discussed options for collecting data and producing estimates of recovery from substance use and mental disorders, including available measures and associated possible data collection mechanisms. This publication summarizes the presentations and discussions from the workshop.

Improving the Quality of Health Care for Mental and Substance-Use Conditions - Institute of Medicine (The National Academies Press, 2006)
Each year, more than 33 million Americans receive health care for mental or substance-use conditions, or both. Together, mental and substance-use illnesses are the leading cause of death and disability for women, the highest for men ages 15-44, and the second highest for all men. Effective treatments exist, but services are frequently fragmented and, as with general health care, there are barriers that prevent many from receiving these treatments as designed or at all. The consequences of this are serious2014for these individuals and their families; their employers and the workforce; for the nation's economy; as well as the education, welfare, and justice systems. Improving the Quality of Health Care for Mental and Substance-Use Conditions examines the distinctive characteristics of health care for mental and substance-use conditions, including payment, benefit coverage, and regulatory issues, as well as health care organization and delivery issues. This new volume in the Quality Chasm series puts forth an agenda for improving the quality of this care based on this analysis. Patients and their families, primary health care providers, specialty mental health and substance-use treatment providers, health care organizations, health plans, purchasers of group health care, and all involved in health care for mental and substance2013use conditions will benefit from this guide to achieving better care.

Advancing Therapeutic Development for Pain and Opioid Use Disorders Through Public-Private Partnerships: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
Chronic pain is one of the most prevalent, costly, and disabling health conditions in the United States. Estimates show that more than 11 percent of the American population suffer from chronic pain, yet the federal pain research investment has been minimal. In parallel with a gradual increased recognition of the problems of treating chronic pain, the opioid epidemic has emerged as a growing public health emergency. The intersection of these two crises lies in the fact that an unintended consequence of treating pain has been an increasing number of opioid prescriptions and diversion of drugs for illicit purposes. In May 2017, the National Institutes of Health (NIH), and the National Institute on Drug Abuse announced a public2013private partnership to develop solutions to the opioid crisis and cut in half the time it takes to develop non-addictive analgesics. To advance the planning of NIH2019s anticipated public2013private partnerships, the National Academies2019 Forum on Neuroscience and Nervous Systems Disorders hosted a public workshop that brought together a diverse group of stakeholders from academia, federal agencies, advocacy organizations and companies developing therapeutics for pain and opioid use disorders. Participants discussed potential strategies to accelerate development of non-addictive pain medications and treatments for opioid use disorders. This publication summarizes the presentations and discussions from the workshop.

Collaboration Between Health Care and Public Health: Workshop Summary - Institute of Medicine (The National Academies Press, 2016)
On February 5, 2015, the Institute of Medicine Roundtable on Population Health Improvement hosted a workshop to explore the relationship between public health and health care, including opportunities, challenges, and practical lessons. The workshop was convened in partnership with the Association of State and Territorial Health Officials (ASTHO)-Supported Primary Care and Public Health Collaborative. Organized in response to the 2012 IOM report Primary Care and Public Health: Exploring Integration to Improve Population Health, this workshop focused on current issues at the interface of public health and health care, including opportunities presented by and lessons learned from the Centers for Medicaid and Medicare Services State Innovation Models program. The workshop featured presentations on several dimensions of the public health-health care relationship. Collaboration Between Health Care and Public Health summarizes the presentations and discussion of the event.

Framing Opioid Prescribing Guidelines for Acute Pain: Developing the Evidence - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
The opioid overdose epidemic combined with the need to reduce the burden of acute pain poses a public health challenge. To address how evidence-based clinical practice guidelines for prescribing opioids for acute pain might help meet this challenge, Framing Opioid Prescribing Guidelines for Acute Pain: Developing the Evidence develops a framework to evaluate existing clinical practice guidelines for prescribing opioids for acute pain indications, recommends indications for which new evidence-based guidelines should be developed, and recommends a future research agenda to inform and enable specialty organizations to develop and disseminate evidence-based clinical practice guidelines for prescribing opioids to treat acute pain indications. The recommendations of this study will assist professional societies, health care organizations, and local, state, and national agencies to develop clinical practice guidelines for opioid prescribing for acute pain. Such a framework could inform the development of opioid prescribing guidelines and ensure systematic and standardized methods for evaluating evidence, translating knowledge, and formulating recommendations for practice.

Methadone Treatment for Opioid Use Disorder: Improving Access Through Regulatory and Legal Change: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine
Methadone is a Food and Drug Administration- (FDA-) approved medication for treating opioid use disorder (OUD), a chronic brain disease that affects more than 2.7 million people in the United States aged 12 and older. Despite its effectiveness in saving lives, many barriers impede access to, initiation of, and retention in methadone treatment for OUD. To address these barriers, on March 3 and 4, 2022, the National Academies of Sciences, Engineering, and Medicine hosted a workshop on \

The Role of Nonpharmacological Approaches to Pain Management: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
Pain is a leading cause of disability globally. The dramatic increase in opioid prescriptions within the past decade in the United States has contributed to the opioid epidemic the country currently faces, magnifying the need for longer term solutions to treat pain. The substantial burden of pain and the ongoing opioid crisis have attracted increased attention in medical and public policy communities, resulting in a revolution in thinking about how pain is managed. This new thinking acknowledges the complexity and biopsychosocial nature of the pain experience and the need for multifaceted pain management approaches with both pharmacological and nonpharmacological therapies. The magnitude and urgency of the twin problems of chronic pain and opioid addiction, combined with the changing landscape of pain management, prompted the National Academies of Sciences, Engineering, and Medicine to convene a workshop on December 420135, 2018, in Washington, DC. The workshop brought together a diverse group of stakeholders to discuss the current status of nonpharmacological approaches to pain management, gaps, and future directions. This publication summarizes the presentations and discussions from the workshop.

Pain Management and Prescription Opioid-Related Harms: Exploring the State of the Evidence: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
On September 22, 2016, the Committee on Pain Management and Regulatory Strategies to Address Prescription Opioid Abuse held a workshop titled 201cPain Management and Prescription Opioid-Related Harms: Exploring the State of the Evidence.201d The purpose of this workshop was to gather information about the state of the science and potential best practices in pain management, including the evolving role of opioids in pain management; to understand the epidemiology of the prescription opioid epidemic and discuss possible strategies to address it; and to identify potential areas for future research in the field. Expert speakers were invited to give brief presentations, which were followed by open discussions among the speakers and workshop participants, including committee members. This Proceedings of a Workshop-in Brief highlights the dialogue that emerged from the individual speakers' presentations and the discussions that followed.

Collaboration Between Health Care and Public Health: Workshop in Brief - Institute of Medicine
Drawing on the experience of practitioners and stakeholders in health and nonhealth fields, the Institute of Medicine's Roundtable on Population Health Improvement fosters interdisciplinary dialogue about factors and actions needed to improve the nation00e220ac2122s health. On February 5, 2015, the roundtable held a workshop in Washington, DC, titled \